ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI LUAS PERMUKAAN DAN VOLUME BALOK DI SMPN 10 PALU BERDASARKAN PROSEDUR NEWMAN’S ERROR ANALISIS DITINJAU DARI JENIS KELAMIN - Caesar Febryawan E. P.; Muh. Hasbi; Dasa Ismaimuza (Universitas Tadulako, 2022)
The purpose of this study is (1) describing students' errors in completing the story about the surface area and volume of blocks based on the Newman error analysis procedure based on gender (2) describe the factors that cause students to make mistakes in solving story problems on the surface area and volume of blocks based on Newman's error analysis procedure in terms of gender.This type of research is qualitative research. The research subjects were 1 male student and 1 female student taken from 31 students of class VIII A. The results of this study indicate that the types of errors made by MH and RS subjects made the same mistakes. The mistakes made were process skills errors and writing errors in answers. The process skill error made by MH is wrong in operating numbers that have variables. MH adds up the two variable numbers 240t + 120t to make 360t2. The process skill error made by RS is wrong in operating numbers that have variables, RS adds up two variable numbers 120 x t + 60 x t to 180 x 2t. MH and RS made mistakes in writing answers, which were not being able to write down the correct units in the final answer. The factors that cause students to make mistakes in solving the problem of surface area and volume of blocks are that students' prerequisite material knowledge is still insufficient or lacking, students are not thorough in solving problems of surface area and volume of blocks, and the inability to determine the right unit.